POLIGAMI KIAI: PRAKTEK POLIGAMI KIAI DI KOTA JEMBER DALAM PANDANGAN KHI DAN GENDER - Anis Nur Arifah (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2016)
Polygamy is a form of marriage that is not prohibited by the religion of Islam. But that does not mean skill, enables a person to polygamy, but requiring them to meet certain conditions and with the right reasons as has been determined in several laws in force in Indonesia, one of its provisions in the Compilation of Islamic Law. However, in fact polygamy became a phenomenon because of the many people who takeit as a final solution, so that the original aim to achieve domestic harmony, becomes a matter that is often considered to damage the rights of women, as well as degrading women by placing an object andnot as a subject that is on par with men in marriage. The fact that we can find in the practice of polygamy Kiai is the purpose of this paper formulation. This study will present some practice polygamy phenomena occurring in society, firstly, how the practice of polygamy Kiai in the town of Jember. Second, how the topography of religiosity in the town of Jember. Third, how the views KHI and Gender to the practice of polygamy Kiai in the town of Jember. The research method used is through a historical approach, geographic, and content analysis to read the practice of polygamy kiai in view of KHI andGender.